HUBUNGAN TINGKAT PENGETAHUAN DAN PERILAKU TENTANG HIGIENE DENGAN KEJADIAN DIARE AKUT - Siahaan, David; Eyanoer, Putri; Hutagalung, Sanggam (Jurnal Kedokteran Methodist, 2020)
Background : Diarrhea is still the main cause of death in the world, accounting for 5-10 million deaths/year. WHO(World Health Organization) estimates there are 4 billion cases that occur worlwide and as many as 2.2 million died, most of which are children under 5 years. In 2016, 5.7 million children died before the age of 5. As many as one in four cases died from diarhhea. Indonesia is one of the developing countries that has problems with diarrheal diseases because of its high prevalence, morbidity, and mortality. Based on the results of a survey by the Ministry of Health in 2016, the number of diarrhea suffers of all ages served in health facilities was 3.176.079 patients and an increase in 2017 was 4.274.790 sufferers or 60.4% of the estimated diarrhea in health facilities. The national incidence of diarrhea for all ages is 270/1.000 population. Methods : The research method used was a literature review, using secondary data. The data were collected using documentation techniques. The research journals used were 16 journals with inclusion criteria in the form of the last 5 year publication, the language used was Indonesian and English, with the research subjects of elementary school children, and full text articles. Conclusion : In accordance with the background and purpose of the literature review of several journals analyzed, it was concluded that there was a relationship between the level of knowledge and behavior about hygiene with the incidence of diarrhea and knowledge of hygiene had an effect on the prevention of diarrhea.